Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3847/psj/acaf6b
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Abundance Derived from Juno MWR and VLA Observations of Jupiter

Abstract: The vertical distribution of trace gases in planetary atmospheres can be obtained with observations of the atmosphere’s thermal emission. Inverting radio observations to recover the atmospheric structure, however, is nontrivial, and the solutions are degenerate. We propose a modeling framework to prescribe a vertical distribution of trace gases that combines a thermochemical equilibrium model with a vertical temperature structure and compare these results to models where ammonia can vary between predefined pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 54 publications
(137 reference statements)
0
32
0
Order By: Relevance
“…This simple “stacked circulation” view (e.g., Fletcher et al., 2020; Tollefson et al., 2019), however, is inconsistent with the banded structure seen here at methane continuum wavelengths longer than 650 nm and may also be inconsistent with retrieved H 2 S abundances (at 1.5 μm) at pressures less than 5 bar (Irwin et al., 2019b), suggesting that the circulation may actually be even more complicated than previously thought. An interesting analogy is the distribution of NH 3 seen in Jupiter's deep atmosphere by the Juno spacecraft (Li et al., 2017), which appears to rise in an equatorial plume, with much greater abundances than at mid‐latitudes, although a more zonal NH 3 structure is seen at the 0.5–2‐bar level by both Juno (Fletcher et al., 2021), and also in mid‐infrared observations (e.g., Fletcher et al., 2016); this is believed to arise and be maintained by a similar double “stacked cell” system (e.g., de Pater et al., 2023; Duer et al., 2021; Fletcher et al., 2021; Ingersoll et al., 2000; Moeckel et al., 2023; Showman & de Pater, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…This simple “stacked circulation” view (e.g., Fletcher et al., 2020; Tollefson et al., 2019), however, is inconsistent with the banded structure seen here at methane continuum wavelengths longer than 650 nm and may also be inconsistent with retrieved H 2 S abundances (at 1.5 μm) at pressures less than 5 bar (Irwin et al., 2019b), suggesting that the circulation may actually be even more complicated than previously thought. An interesting analogy is the distribution of NH 3 seen in Jupiter's deep atmosphere by the Juno spacecraft (Li et al., 2017), which appears to rise in an equatorial plume, with much greater abundances than at mid‐latitudes, although a more zonal NH 3 structure is seen at the 0.5–2‐bar level by both Juno (Fletcher et al., 2021), and also in mid‐infrared observations (e.g., Fletcher et al., 2016); this is believed to arise and be maintained by a similar double “stacked cell” system (e.g., de Pater et al., 2023; Duer et al., 2021; Fletcher et al., 2021; Ingersoll et al., 2000; Moeckel et al., 2023; Showman & de Pater, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…(2019) and Moeckel et al. (2023), along with (2.12) and (2.13) to obtain first guesses of , and as shown by the blue dots in figure 2. Although the temperature data appear to be smooth, when we differentiate to compute with (2.25 a , b ), we find that it is not smooth, especially at heights deeper than mbar (see the blue dots in figure 2 d ).…”
Section: Choice Of Hydrostatic Fieldsmentioning
confidence: 97%
“…Our calculations are carried out using the observed atmospheric temperature and pressure (de Pater et al. 2019; Moeckel, de Pater & DeBoer 2023), which consists of a highly stratified region at heights above a convection zone (see § 3 for details). The atmosphere is highly stratified at the top of our computational domain and has , where is the Brunt–Väisälä frequency of the atmosphere, and is the local Coriolis frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The data are plotted as ratios to solar abundances (Lodders 2019). For the Jovian N/H 2 ratio, we use an NH 3 abundance of -+ 340 17 27 ppmv (Moeckel et al 2023), to which we add the putative NH 4 SH cloud using H 2 S, as reported by the Galileo Probe (Wong et al 2004). The open blue triangle is a Juno inference of equatorial H 2 O (Li et al 2020).…”
Section: Uranus Inspired By Jupitermentioning
confidence: 99%